2019
DOI: 10.1128/jvi.02066-18
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ongoing Influenza A Virus Replication Reveals Different Mechanisms of RIG-I Activation

Abstract: Pattern recognition receptors provide essential nonself immune surveillance within distinct cellular compartments. Retinoic acid-inducible gene I (RIG-I) is one of the primary cytosolic RNA sensors, with an emerging role in the nucleus. It is involved in the spatiotemporal sensing of influenza A virus (IAV) replication, leading to the induction of type I interferons (IFNs). Nonetheless, the physiological viral ligands activating RIG-I during IAV infection remain underexplored. Other than full-length viral geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…In particular, it has been shown that svRNA synthesis can influence vRNA synthesis by binding to the viral RNA polymerase (Perez et al 2012). The viral nonstructural protein 2 (NS2/NEP) may be involved in regulating svRNA expression (Perez et al 2010;Liu et al 2019).…”
Section: ; Liumentioning
confidence: 99%
“…In particular, it has been shown that svRNA synthesis can influence vRNA synthesis by binding to the viral RNA polymerase (Perez et al 2012). The viral nonstructural protein 2 (NS2/NEP) may be involved in regulating svRNA expression (Perez et al 2010;Liu et al 2019).…”
Section: ; Liumentioning
confidence: 99%
“…They retain the 5= and 3= genomic noncoding regions and thus the same panhandle structure activating RIG-I. While several lines of evidence argue against IFN induction by incoming vRNPs (41,55,56), chemical inhibition of ongoing viral replication reveals the direct contribution of incoming DI RNA as contained in the IAV stocks to RIG-I activation and IFN induction (Fig. 2, step 1) (56).…”
mentioning
confidence: 97%
“…While several lines of evidence argue against IFN induction by incoming vRNPs (41,55,56), chemical inhibition of ongoing viral replication reveals the direct contribution of incoming DI RNA as contained in the IAV stocks to RIG-I activation and IFN induction (Fig. 2, step 1) (56). The mechanism for the preferential RIG-I sensing of incoming DI RNA over vRNP is currently unknown but likely lies in the level of exposure of the panhandle structure and/or its cellular distribution.…”
mentioning
confidence: 99%
See 2 more Smart Citations